Contextos estratigráficos de la cerámica recuay: una perspectiva desde Huamparán, sierra oriental de Áncash - Ibarra Asencios, Bebel; Escobar Silva, Carlos; Cruz Quiñones, Jhon (Pontificia Universidad Católica del Perú, 2025)
This case report correlates the types of ceramic wares and the stratigraphy of the Recuay site of Huamparán in the Callejón de Conchucos, Ancash. It was concluded that the various ceramic types were not in sequential but coetaneous use throughout the three phases of occupation (200 B.C.-A.D. 900). The predominance of ceramic types with shashal all throughout the Recuay sequence suggests that sociopolitical changes did not alter the manufacture of ceramics using this material, which endured throughout all of the Late Intermediate Period. Some types likewise suggest non-local manufacture and interrelations with other groups, both coastal and from the northern highlands.

Este reporte de caso correlaciona los tipos de pastas cerámicas con la estratigrafía del sitio recuay de Huamparán, ubicado en el Callejón de Conchucos, Áncash. Como resultado, se concluye que los diversos tipos cerámicos no tuvieron un uso secuencial, sino coetáneo, durante las tres fases de ocupación (200 a.C.-900 d.C.). El predominio de los tipos de cerámica con shashal a lo largo de la secuencia recuay sugiere que los cambios sociopolíticos no alteraron la producción de cerámica con este material, que continuó durante todo el Período Intermedio Tardío. Asimismo, algunos tipos sugieren una manufactura no local e interrelaciones con otros grupos de la costa y la sierra norte.
Stratigraphic contexts of Recuay ceramics: a perspective from the Huamparán site in the eastern mountains of Ancash
Keywords: Recuay; Ceramics; Shashal; Ancash; Caolin; Recuay; Cerámica; Shashal; Áncash; Caolín; https://purl.org/pe-repo/ocde/ford#6.01.02